2012
DOI: 10.1016/j.eurpsy.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing recovery from schizophrenia as an individual process. A review of self-report instruments

Abstract: The Recovery Assessment Scale is possibly the best currently available measure of personal recovery when all evaluation criteria are included. However, the ratings listed in the current paper depended on the availability of information and the quality of available reports of previous assessment of the measurement properties. Considering the significant amount of information lacking and inconsistent findings, further research on the reviewed measures is perhaps more important than the development of new measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 101 publications
4
82
1
1
Order By: Relevance
“…In our study no significant association was found between thought disorder and patients' subjective experiences of recovery as measured by the RAS subscales. However, this result is consistent with the broad consumer literature espousing that personal recovery is possible even in the presence of disabling symptoms (Cavelti et al, 2012b;Salzer and Brusilovskiy, 2014).…”
Section: Discussion Of the Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In our study no significant association was found between thought disorder and patients' subjective experiences of recovery as measured by the RAS subscales. However, this result is consistent with the broad consumer literature espousing that personal recovery is possible even in the presence of disabling symptoms (Cavelti et al, 2012b;Salzer and Brusilovskiy, 2014).…”
Section: Discussion Of the Resultssupporting
confidence: 90%
“…From consumers' perspective, recovery refers to a personal process of overcoming the negative personal and social consequences of having a severe mental disorder and regaining a self-determined and meaningful life, beyond symptom remission and functional rehabilitation (Bellack, 2006). Thus, recovery is no longer seen as an event occurring solely within the individual, but as a dynamic interplay between the individual and its environment (Cavelti et al, 2012b). In this article, we will refer to the latter definition of recovery as "personal recovery" (Slade et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The RAS was implemented across a number of countries, therefore accomplishing a sound empirical evidence base (Cavelti et al, 2012;Salzer & Brusilovskiy, 2014;Shanks et al, 2013).…”
mentioning
confidence: 99%
“…The Recovery Assessment Scale has been suggested as the best available measure (e.g. [28,29]). Interestingly, along with the evolution of assessment measures for personal recovery, the recovery orientation of mental health services has also been of major interest in research, with several measures being developed (for a review see [31]).…”
Section: Integrated Assessment Of Psychosis: Assessment Tools Derivedmentioning
confidence: 99%
“…With the intention of summarizing and critically analyzing data for the existing measures, several comprehensive and integrative systematic reviews on existing and psychometrically tested self-report measures specifically developed for severe mental illness, mainly psychotic disorders emerged [28][29][30]. The Recovery Assessment Scale has been suggested as the best available measure (e.g.…”
Section: Integrated Assessment Of Psychosis: Assessment Tools Derivedmentioning
confidence: 99%